Aesthetics of Rhythmic Formation in Prose Poem of Amjed Nasser - Ako Rshideh, Abdelsalam Abdelkarem; Alkhresheh, Ahmed Ghaleb (Journal of Arabic Language Sciences and Literature, 2022)
The purpose of this research is to explore the aesthetics of rhythmic formation in the prose poem of Amjad Nasser, who is considered one of the most prominent Jordanian poets who dominated this poetic color over their poetic production, as he was able to transform his poetic experience from the activating poem to the prose poem that dispensed with the rhythm of meter and rhyme; depending on other rhythmic that preserve its poetic notion. The research adopted the analytical method in this research and came in two sections, the first of which dealt with the internal vocal rhythm, and the internal rhythm of the words, while the second section dealt with the semantic rhythm of the words, and the semantic rhythm of the title. The findings showed that Amjed Nasser was able to employ the rhythmic techniques of the prose poem, contributing in giving his textsa rhythmic fabric that carried his thoughts and visions that he wanted to express.
Keywords: Rhythmic Formation; Prose Poem; Amjad Nasser